Indirect robust totally decentralized adaptive control of continuous-time interconnected systems - Wen, Changyun (IEEE transactions on automatic control, 1995)
This paper presents a global stability result on continuous-time indirect totally decentralized adaptive control systems. The algorithms employed in the design of local adaptive controllers are earlier basic conventional adaptive control algorithms subject to parameter projection operation. For the first time, it is shown that without any restriction on signals such as persistence of excitation, global boundedness of the signals in the overall continuous-time feedback system is guaranteed. For implementation, no a priori knowledge on the interactions and unmodeled dynamics is required.< >